The Specters of Marx in Edward Said’s Orientalism - Sing, Manfred (Die Welt des Islams, 2013)
Edward Said’s Orientalism was not only an attack on Western scholarship and imperialism, but also on Marxism. Said depicted Karl Marx as yet another Orientalist, Marxism as a form of Western domination and Arab Marxism as an expression of Self-Orientalization. Said claimed to have surpassed Marxism and Marxists who were “blinded to the fact of imperialism”. Said’s ambivalent relation to Marxism has not been thoroughly studied until now although it forms an important cornerstone in his argumentation and self-representation. This lacuna is surprising since many early Arab critics of Orientalism came from a Marxist background. Said either ignored them or rebuffed their interventions as “dogmatist”. The following article analyzes the nature of the conflict between the two sides and their underlying differences and reflects on the conditions affecting the Arab reception of Orientalism.